Longitudinal and transverse muscle stiffness change differently with knee osteoarthritis and do not align with stiffness sensation - Dieterich, Angela V.; Skerl, Katrin; Paskali, Filip; Gizzi, Leonardo; Azan, Mehrin; Carvalho, Gabriela F.; Kohl, Matthias; Haueise, Andreas (Frontiers in Physiology, 2025)
Knee osteoarthritis (OA) is a prevalent joint condition associated with disability, pain, and stiffness in the muscles surrounding the knee. Myofascial and massage techniques are employed to alleviate these symptoms. Unclear is whether muscle stiffness is measurably increased in the painful muscles, and how measured muscle stiffness relates to perceived stiffness, pain, and functional impairment. Given muscle anisotropy, stiffness changes may occur in the longitudinal plane parallel to muscle fibers or perpendicularly in the transverse plane. Shear wave velocity (SWV) was measured in both scanning planes in 21 individuals with diagnosed knee OA, 21 sex- and age-matched controls, and 20 young controls, focusing on the gastrocnemius medialis and vastus lateralis muscles under four conditions: (a) resting state, (b) holding the shank against gravity, (c) double-leg stance, and (d) single-leg stance. Median stiffness measures, the ratio of longitudinal-to-transverse stiffness, and the ratio of single-leg stance-to-baseline stiffness were compared between groups using the Kruskal- Wallis and Pairwise Asymptotic Wilcoxon rank sum tests. Correlations with the Knee Injury and Osteoarthritis Outcome Score and the Tampa Scale of Kinesiophobia were examined. Longitudinal stiffness of the gastrocnemius medialis muscle was significantly lower in the OA group at double-leg (P = 0.033) and single-leg stance (P = 0.019), with tendencies toward lower median stiffness in both muscles across most tasks. Transverse stiffness of the vastus lateralis muscle was significantly higher in the OA group at baseline (P = 0.027), with tendencies toward higher median stiffness in both muscles across most tasks. Significant moderate to excellent correlations support the clinical relevance of both longitudinal and transverse stiffness measurements. Measured and perceived stiffness were not correlated. Study results suggest that knee OA may differentially affect muscle stiffness in the longitudinal and transverse planes and that transverse stiffness measures may have clinical relevance.